Net Clinical Benefit of Direct Oral Anticoagulants in Patients With Cancer and Venous Thromboembolism: A Systematic Review and Trade-Off Analysis - Yan, Yi-Dan; Ding, Zheng; Pan, Mang-Mang; Xia, Qing; Cui, Jiu-Jie; Wang, Li-Wei; Zhang, Chi; Gu, Zhi-Chun (Frontiers in Cardiovascular Medicine, 2020)
Background: Venous thromboembolism (VTE) is highly prevalent in cancer patients. Recent guidelines recommend considering direct oral anticoagulants (DOACs) for the treatment of cancer-associated thrombosis (CAT). However, direct head-to-head comparisons among DOACs are lacking, and almost no net clinical benefit (NCB) analysis has been performed in patients with CAT. Methods: We systematically searched PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov for randomized controlled trials (RCTs) reporting on recurrent VTE, major bleeding, or clinically relevant bleeding events in patients with CAT who received DOACs and low-molecular-weight heparins. Relative risks (RRs) and 95% confidence intervals (95% CIs) were calculated using a random-effect model. Surface under the cumulative ranking curve (SUCRA) values were calculated, and a trade-off analysis was performed to estimate the NCB. Results: Overall, four RCTs involving 2,894 patients were enrolled. DOACs were more effective than dalteparin in reducing the risk of recurrent VTE (RR: 0.62, 95% CI: 0.44–0.87), with a comparative risk of major bleeding (RR: 1.33, 95% CI: 0.84–2.11) and an increased risk of clinically relevant bleeding (RR: 1.45, 95% CI: 1.05–1.99). No significant difference was observed among individual anticoagulants in terms of recurrent VTE and major bleeding. With respect to the ranking of each anticoagulant for the primary outcome, edoxaban (SUCRA: 69.2) was more effective than dalteparin (SUCRA: 60.7), rivaroxaban (SUCRA: 60.7), and apixaban (SUCRA: 25.5) in reducing VTE recurrence. For major bleeding, apixaban (SUCRA: 76.3) had the highest cumulative ranking probability, followed by edoxaban (SUCRA: 66.4), dalteparin (SUCRA: 28.8) and rivaroxaban (SUCRA: 28.5). Similar results were observed for clinically relevant bleeding. In terms of both benefit and safety outcomes, DOACs, especially edoxaban, seemed to confer a better NCB profile than dalteparin. Conclusions: DOACs are a safe and effective alternative therapy to dalteparin in patients with CAT. Among them, edoxaban might provide a good risk-to-benefit balance. However, because of the lack of head-to-head studies, further investigations are needed to confirm our findings.